2016
DOI: 10.1007/s10853-016-0456-9
|View full text |Cite
|
Sign up to set email alerts
|

New understanding of the shape-memory response in thiol-epoxy click systems: towards controlling the recovery process

Abstract: Our research group has recently found excellent shape-memory response in “thiol-epoxy” thermosets obtained with click-chemistry. In this study, we use their well-designed, homogeneous and tailorable network structures to investigate parameters for better control of the shape-recovery process. We present a new methodology to analyse the shape-recovery process, enabling easy and efficient comparison of shape-memory experiments on the programming conditions. Shape-memory experiments at different programming condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
(7 reference statements)
1
16
0
Order By: Relevance
“…As explained above, formulations containing SU8 show higher ∆ T peak due to the broader relaxation process as deduced from the FWHM values in Table 2 . These results point out the close relation between network relaxation and shape-recovery in glassy materials, as previously observed [ 22 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As explained above, formulations containing SU8 show higher ∆ T peak due to the broader relaxation process as deduced from the FWHM values in Table 2 . These results point out the close relation between network relaxation and shape-recovery in glassy materials, as previously observed [ 22 ].…”
Section: Resultssupporting
confidence: 89%
“…Moreover, these materials are potential candidates for shape-memory applications. On the one hand, it has been shown that the “thiol–epoxy” network leads to SMPs with enhanced response: high performance fixing and recovering the original shape, rapid recovery-process, high strength and extended deformation limits [ 21 , 22 , 23 ]. On the other hand, thanks to the possibility of forming complex-shaped designs, the final material is an interesting candidate for many of the mentioned applications.…”
Section: Introductionmentioning
confidence: 99%
“…The value of R r slightly decreases as the IPDI content increases, obtaining the lowest R r with the material completely based on IPDI. This is probably due to a stress hardening process taking place during the loading process that generates permanent deformation in the network structure after programming the temporary shape [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among SMPs, thermoset-based SMPs are increasingly studied for their easy processing, durability, and superior thermal and mechanical performance in comparison to common shape-memory elastomers or thermoplastic-based SMPs [ 14 , 15 ]. In particular, high-performance shape memory thermosets (HPSMTs) are particularly interesting for industrial applications, since they can perform mechanical work against external loads [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…2b, the characteristic monomer peak, epoxy peak (910 cm -1 ) in E51, and thiol peak (2566 cm -1 ) in Tetra-SH disappeared in the spectra of the vitrimers, while the hydroxyl peak (3200-3600 cm -1 ) appeared. 40,41 The FT-IR spectra of the vitrimers and ESMTW samples exhibited high similarity, indicating that a high content of vitrimers filled the porous structures of the DW scaffold. The density of the ESMTW was approximately 1.232 g cm -3 .…”
Section: Resultsmentioning
confidence: 97%